Understanding the tax practitioner-client relationship: Using a role theory framework - Tan, Lin Mei (Elsevier Ltd., 2014)
Adapting the Role Episode Model, this paper presents a conceptual framework by which the tax practitioner-client encounters can be understood and analysed. The framework is focused on the tax practitioner and the client and the role process consists of a set of demands made by taxpayers on their practitioners. Practitioners also have their own views of what demands they should try to meet, given their type of social position. The characteristics of taxpayers and of tax practitioners, their interpersonal relations, and features of decision context that may have an impact on their decision making are all taken into consideration.